Impact of health education on awareness of sedentary lifestyle as predisposing factor to cardiovascular diseases among secondary school principals in zone 4, Nigeria (2018)
Skeletal muscles contract to produce body movement Essentially, skeletal muscle activities affect the health of other organs such as heart, adipose tissue, brain. Engaging in physical exercise enhances proper functioning of body organs, thus promoting healthy living. Nigerian secondary school principals are not known to engage in physical exercise, probably due to poor awareness of its importance to their health. Meanwhile, a life of inactivity otherwise called sedentary lifestyle is a risk factor to cardiovascular disease. In recent times, cardiovascular disease has led to a significant increase in deaths among administrators in Nigeria. Therefore, this study examined impact of Health Education on awareness of sedentary life style as predisposing factor to cardiovascular diseases among secondary school principals in zone 4, Oyo State, Nigeria. The study adopted a single group pre-test-post-test quasi experimental research design. Participants were given Health education on sedentary lifestyle and related diseases as its resultant effect. A split plot analysis of variance (SPANOVA) was employed to find the difference in pre-test-post-test scores of the participants. The result showed that, health education given was effective. The participants’ awareness level increased, thus willing to refrain from sedentary lifestyle and adopt a sporting lifestyle. It was recommended that, the Ministry of Education should mandate school managements to create time during the school hours for principals and members of staff to engage in physical exercises. Also, health education in which disease prevention will feature prominently should form part of the agenda during meetings of school principals.